The impacts of International Financial Crisis on Saudi Arabia Economy: Evidence from Asymmetric SVAR modelling - Ghassan, Hassan B.; Alhajhoj, Hassan R.; Alaoui, Mohammed Kbiri (Journal of Reviews on Global Economics, 2013)
This paper aims to measure the impacts of International Financial Crisis on the performance of the Saudi Arabian economy from 1968 to 2010. Linear and non-linear SVAR methodologies are used to exhibit the interdependence between the process of international liquidity, net-exports and economic growth. The empirical models show that the impacts of international financial crisis lead to an immediate drop in the net-exports and conduct to reduce gradually real economic growth during roughly three years. In the horizon, the variation in economic growth is largely attributed to domestic supply shocks, but negative shocks of international financial markets drove to reduce the economic growth in the long-run by 1.04%